2009
DOI: 10.1007/s11864-009-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and Oropharyngeal Cancer: What You Need to Know in 2009

Abstract: Oropharyngeal cancer has demonstrated a steady increase in incidence over the past 20 years in contrast to declining numbers of head and neck squamous cell carcinoma (HNSCC) overall. Recent evidence has found that high-risk strains of human papillomavirus (HPV) are the likely cause of the changing epidemiology of oropharyngeal cancer. HPV-associated oropharyngeal cancer has a molecular, epidemiological, and clinical profile that is distinct from non-HPV HNSCC. Clinicians managing oropharyngeal HNSCC need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 36 publications
4
49
0
1
Order By: Relevance
“…Several authors have emphasized that a hallmark of the presence of HPV in cancer could be found in p16 nuclear or cytoplasmic overexpression, so that p16 could be considered a useful surrogate marker for HPV (Gillespie et al, 2009;Goon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have emphasized that a hallmark of the presence of HPV in cancer could be found in p16 nuclear or cytoplasmic overexpression, so that p16 could be considered a useful surrogate marker for HPV (Gillespie et al, 2009;Goon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the Surveillance, Epidemiology and End Results (SEER) database revealed that the incidence rates for HPV at the base of the tongue and in the tonsils increased by 2% and 4%, respectively, between 1973 and 2001 in younger US populations (ages 20-44 years). At the same time, the incidence in all other oral and pharyngeal sites remained constant or decreased (Gillespie et al, 2009). Other countries, such as Sweden, have seen a similar increase in the incidence of tonsil cancer from 1997-2002; HPV could be isolated in 23% of specimens in the 1970s, 28% in the 1980s, 57% in the 1990s and 68% in specimens since 2000 (Hammarstedt et al, 2006).…”
Section: Hpv and Oral Lesionsmentioning
confidence: 96%
“…Some evidence has indicated that some subtypes of HPV are linked to head and neck cancer, especially those arising from some oropharyngeal subsites (e.g., tonsil and the base of the tongue) (Gillespie et al, 2009). The overall HPV prevalence in HNSCC ranges from 3% to 40% and could vary more according to the specific site.…”
Section: Hpv and Oral Lesionsmentioning
confidence: 99%
See 2 more Smart Citations